MACROSOMIA, OBESITY, MACROCEPHALY AND OCULAR ABNORMALITIES (MOMO SYNDROME) IN 2 UNRELATED PATIENTS - DELINEATION OF A NEWLY RECOGNIZED OVERGROWTH SYNDROME - Morettiferreira, D.; Koiffmann, C. P.; Listik, M.; Setian, N.; Wajntal, A. (Wiley-Blackwell, 1993)
We describe 2 unrelated patients, a boy and a girl, with an overgrowth syndrome and the following common characteristics: macrocrania, obesity, ocular abnormalities (retinal coloboma and nystagmus), downward slant of palpebral fissures, mental retardation, and delayed bone maturation. Both cases are of sporadic occurrence with no consanguinity between the parents. We suggest that this syndrome is due to a new autosomal dominant mutation and propose to designate it with the acronym of ''MOMO syndrome'' (Macrosomia, Obesity, Macrocrania, Ocular anomalities).
Keywords: OVERGROWTH; OBESITY; MACROCRANIA; AUTOSOMIC DOMINANT; MENTAL RETARDATION; RETINAL COLOBOMA